PENGARUH GAYA KEPEMIMPINAN PARTISIPATIF DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI BPKAD KOTA PONTIANAK - B31111064, JULIO PRATAMA PUTRA (Jurnal Manajemen Update, 2017)
The purpose of this study was to examine the influence of participative leadership style and organizational culture on employee performance BPKAD Pontianak. The sample in this study was 69 employees BPKAD Pontianak. The analytical method used is descriptive quantitative method. Data were analyzed with multiple linear regression, and using SPSS version 16.0. Results of the analysis showed that the value of the coefficient of determination obtained indicates a value of 0.334, which means that the influence of participative leadership style and cultural organization can contribute to the performance by 33,4% while the rest influenced by other factors outside the research. The result of f test analysis showed a significant with a value 0,000. The results of t test analysis showed a participatory leadership style have a significant effect on performance, with a value of t = 2.827 greater than the value table = 1.668. And cultural organization significant effect on performance, with a value of t = 2.353 greater than the value table = 1.668 Â  Keywords : Participative Leadership Style, Cultural Organization, Employess performence